2014
DOI: 10.1007/s11605-014-2673-3
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Laparoscopic Cholecystectomy Inpatient Analysis: Does the End Justify the Means?

Abstract: LOS of RAC is similar to LC. Cost of RAC remains higher compared to LC although there was reduction in cost of RAC in 2011 versus 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Current average cost for robotic instruments and accessories used during major pancreatic resection adds $2,007 to operative costs, an estimate significantly lower than $3,330 as reported by Butturini et al (31). Further, a link between cost and case experience has been observed consistent with a learning curve effect; robotic surgery costs decreased 14.6% between 2011 ($23,595) and 2010 ($19,528) while laparoscopic costs remained stable ($15,286 and $15,195) (43).…”
Section: The Coming Renaissancementioning
confidence: 77%
See 2 more Smart Citations
“…Current average cost for robotic instruments and accessories used during major pancreatic resection adds $2,007 to operative costs, an estimate significantly lower than $3,330 as reported by Butturini et al (31). Further, a link between cost and case experience has been observed consistent with a learning curve effect; robotic surgery costs decreased 14.6% between 2011 ($23,595) and 2010 ($19,528) while laparoscopic costs remained stable ($15,286 and $15,195) (43).…”
Section: The Coming Renaissancementioning
confidence: 77%
“…A large population-based study conducted by Kamiński et al examined differences in surgical outcomes and cost between robotic and laparoscopic cholecystectomies using 2010 and 2011 data from the National Inpatient Sample Health Cost Utilization Project (43). While length of stay and complication rates were similar, total hospital costs in the robotic group ranged from $4,333 to $8,310 higher than the laparoscopic group, despite excluding amortization costs for the robotic system.…”
Section: Rcmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on robotic surgeries cost and clinical outcomes are procedure-specific; therefore, robotassisted outcomes have not shown consistent benefits, whereas other authors support robotassisted over standard laparoscopy for cholecystectomies [4]. Salman et al reviewed a national database and showed that robotic surgery had significantly shorter lengths of stay than open surgery and had lower charges than laparoscopic and open surgery [7].…”
Section: Discussionmentioning
confidence: 99%
“…There was less emphasis on other aspects of the clinical outcomes. Certain robotic procedures have already been shown to have better operative outcomes compared with open surgery in terms of length of hospital stay (LOS), complications and mortality, yet many studies comparing laparoscopic with robot-assisted surgeries have produced conflicting results in terms of clinical outcomes and cost-effectiveness [3][4][5][6]. Cholecystectomy is one of the most common procedures where the robot-assisted approach has been used.…”
Section: Introductionmentioning
confidence: 99%